Neuromuscular efficiency during double poling at increasing velocity and inclination in cross-country and biathlon skiers - Pozzo, R.; Besseghini, A.; Cas, F. D.; Rossi, G.; Canclini, A.; Canclini, A. (9th International Congress on Science and Skiing, March 18 - 22, 2023, Saalbach-Hinterglemm, Austria, 2023)
INTRODUCTION: Double poling (DP) is one of the most used techniques in cross-country skiing and very reliable model to study biomechanical and physiological performance characteristics. Increasing speed and inclination significantly affects mechanical and neuromuscular output (Holmberg et al., 2005; Lindinger et al., 2011; Sandbakk et al., 2010). The purpose of this study is to investigate the strategy of neuromuscular patterns with respect to the variation of external load.